Gamified Vocabulary Learning through Quizizz: An Experimental Study on EFL Students’ Lexical Development in Indonesia - Syarif Hidayat Nasir; Ashabul Kahfi Susanto; Vivin Helvira; Aqzhariady Khartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This experimental study investigates how gamified vocabulary learning through Quizizz supports English as a Foreign Language (EFL) students’ lexical development in Indonesia. Grounded in the principles of Self-Determination Theory, the research examines how game-based features, such as instant feedback, competition, and reward systems, enhance learners’ motivation and engagement during vocabulary acquisition. Twenty-eight eleventh-grade students from a public school in South Sulawesi participated in pre- and post-tests to measure learning gains after the Quizizz intervention. The results indicate notable improvements in students’ vocabulary mastery accompanied by increased autonomy and active participation during lessons. The findings suggest that integrating gamification elements can strengthen learners’ intrinsic motivation, contributing to more effective vocabulary learning in EFL classrooms. However, the study’s limited context, focusing on a single school and lacking comparison with other digital platforms, constrains the generalizability of the results. The study recommends broader implementation and future research across varied educational settings to further validate the potential of Quizizz and similar tools in enhancing EFL students’ lexical resources.